Is guanxi belief predicted by system-justifying ideologies? Exploring the relationship of guanxi belief with meritocratic ideology, social dominance orientation and right-wing authoritarianism (¿Son las ideologías justificativas del sistema predictoras de la creencia en el guanxi? Exploramos la relación de la práctica guanxi con la ideología meritocrática, la orientación a la dominación social y el autoritarismo de derecha). Issue 2 (4th May 2021) - Liu, Haoxin; Wang, Tulips-Yiwen; Bernardo, Allan B. I.
ABSTRACT: Some scholars view guanxi as having an important role in social transactions in Chinese societies, while others view guanxi as a problematic practice associated with unfairness and inequality. We propose that the belief in guanxi is a societal norm that is part of the social system in Chinese society, and that belief in guanxi as a social norm is associated with Chinese people's system-justifying beliefs. Chinese university students completed scales on guanxi belief, meritocratic ideology (MI), social dominance orientation (SDO), right-wing authoritarianism (RWA) and their subjective socioeconomic status. Regression analysis indicated that guanxi belief has significant positive relationships with the other three system-justifying ideologies, supporting the proposal that guanxi belief is part of the societal systems supported by people who hold hierarchy-enhancing ideologies.